2017
DOI: 10.2308/accr-51696
|View full text |Cite
|
Sign up to set email alerts
|

Do Social Ties between External Auditors and Audit Committee Members Affect Audit Quality?

Abstract: We examine whether social ties between engagement auditors and audit committee members shape audit outcomes. Although these social ties can facilitate information transfer and help auditors alleviate management pressure to waive correction of detected misstatements, close interpersonal relations can undermine auditors' monitoring of the financial reporting process. We measure social ties by alma mater connections, professor-student bonding, and employment affiliation, and audit quality by the propensity to ren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
88
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(98 citation statements)
references
References 137 publications
3
88
0
7
Order By: Relevance
“…Committee level researches are heavily focused on the benefits of audit, nomination and remuneration committees within the BoDs because of the high risks of conflicts of interest characterizing these areas. In fact, the key role played by the board committees is to manage potential conflicts of interest supporting the BoDs in its decision-making process [10,12,39,40]. Other ad-hoc committees for specific tasks can be established.…”
Section: The Role Of Csr Committeesmentioning
confidence: 99%
“…Committee level researches are heavily focused on the benefits of audit, nomination and remuneration committees within the BoDs because of the high risks of conflicts of interest characterizing these areas. In fact, the key role played by the board committees is to manage potential conflicts of interest supporting the BoDs in its decision-making process [10,12,39,40]. Other ad-hoc committees for specific tasks can be established.…”
Section: The Role Of Csr Committeesmentioning
confidence: 99%
“…These authors have used these quality factors, which restrict the production of high-quality corporate financial reports, as evidence in the collapse of financial reporting. To increase the quality of financial reporting and reduce the chances of intentional EM, researchers have focused on the CG environment by testing whether corporate boards [36][37][38][39], ACs [40][41][42], external auditors [43][44][45], and internal auditors [46][47][48], exert their individual or collective influence on the formulation of financial reports that are free from misrepresentation and show the true financial position of the firm. Prior research [4,49,50], indicated that a higher quality of reported earnings depends on the efficient CG mechanism of the firms, which ultimately results in the reduction of manipulated accruals which divulge the need for efficient and effective Boards of Directors (BODs).…”
Section: Earnings Management and Corporate Governancementioning
confidence: 99%
“…Because of major accounting scandals around the 2000s, regulators are increasingly concerned with the effectiveness of audit committees in monitoring corporate financial reporting and internal controls. Prior research suggests that audit committees' characteristics including committee size (e.g., Anderson et al ; Karamanou and Vafeas ), independence (e.g., Carcello and Neal , ; Klein ; Cassell et al ), meeting frequency (e.g., Anderson et al ; Chen and Zhou ), legal expertise (Krishnan et al ), and social ties with external auditors (He et al ) influence audit committee quality and effectiveness in fulfilling their monitoring obligations. In particular, prior research suggests that financial expertise enhances audit committee monitoring effectiveness (Krishnan ; Zhang et al ; Hoitash et al ).…”
Section: Introductionmentioning
confidence: 99%